Crises in Education: Reflections on the Conflation of Education with Economics and Politics - Jeffrey Goldfarb (University of Lower Silesia, 2013)
In his reflection on the global crisis in education, the author points to the growing conflation of education with economics and politics and considers a generally neglected dimension of worldwide educational crisis, namely, the persistent lack of appreciation of education as a significant end in itself. He illustrates his point on three national cases - the United States, Israel and Poland - and shows the current crisis as a general attack using the life of the mind and the role it plays in the life of society and individuals.